A novel biostimulant obtained from red wine lees enhances tolerance to ozone-induced abiotic stress in grapevine plants - Naranjo, Emilia; Orts, Angel; Orts, José M.; Martin-Presas, Luis; Castaño, Angélica; Parrado, Juan (Frontiers in Plant Science, 2026)
The main objective of this study was to investigate the ability of a novel plant biostimulant obtained from red wine lees by enzymatic hydrolysis (LEE) to protect against abiotic ozone damage in grapevine plants (Vitis vinifera). Tropospheric ozone at high concentrations is considered a pollutant that harms plants by entering through the leaves via the stomata. Once inside, it decomposes into reactive oxygen species (ROS), causing oxidative stress, reduced photosynthesis, growth alterations, and visible symptoms such as necrotic spots and yellowing. LEE counteracted ozone-induced damage, as evidenced by net photosynthetic rate, electron transport rate, effective quantum yield of Photosystem II, and delayed fluorescence. LEE triggered the overexpression of genes involved in the synthesis of secondary metabolites that reduce oxidative damage and enhance resilience. Additionally, it decreases energy expenditure on emergency responses, as shown by the lower expression of stress-related genes. Consequently, the biostimulant optimizes metabolic efficiency and plant health.